THE ESTABLISHMENT OF LEGAL RULES AS AN ELEMENT OF THE SYSTEM OF LEGAL INFLUENCE: AN INSTRUMENTAL APPROACH - L. Berg (BRICS Law Journal, 2018)
The author considers the essence of the establishment of legal rules as the will of the State that forms the structure of social relations. Based on an instrumental approach, the author examines the establishment of legal rules and the rules of law in their interaction with social activity, which allows subjects to “find themselves” in the legal system. Thus, the structures of public authorities, establishments and enterprises are created, their goals and order of activities are determined, as well as the competence and powers of officials, and legal statuses are secured; consequently, the participants, objects, terms of starting, changing and terminating legal relations concerning society are determined, too. Hence, the law influences the content of social relations, which is activity. In general, the results of the activities of individual and collective subjects of law reflect social relations, and social relations need legal regulation. At the same time, social relations may appear not only as activity, they may also appear in a passive form as legal statuses, social institutions. They are also regulated through legal rules, and in that case legal influence is carried out through the establishment of legal rules. It is able to predict the legal forms of subject activities through the establishment of legal rules. The author puts forward a legal definition of the establishment of legal rules as a purposeful influence on public relations, which is to regulate by means of legal rules. Distinctions of legal regulation from legal influence are established. The legal means expressing external factors in reference to the subject’s will correspond to the establishment of legal rules. However, by analyzing a list of normative acts we can conclude that legal means should be established more logically. It is necessary to consider the dialectics of relationships between purpose and means in the field of rulemaking processes, since dialectics is of a two-way determinative nature.